Successful liver transplantation for drug-induced vanishing bile duct syndrome. Issue 1 (15th January 2020) - Hashim, Ahmed; Barnabas, Ashley; Miquel, Rosa; Agarwal, Kosh
Abstract : Drug-induced cholestasis has a wide range of clinical presentations, and in a small number of patients, it can progress to severe ductopenia. A 63-year-old woman was referred to our department with progressive cholestasis and hyperbilirubinaemia following a course of flucloxacillin. Despite the comprehensive laboratory, imaging and genetic investigations, no other cause for the cholestasis was demonstrated. Sequential liver biopsies confirmed the development of vanishing bile duct syndrome. She developed significant cachexia and pruritus that did not respond to medical therapy, and hence she was listed for liver transplantation. She underwent liver transplantation 6 months after the initial drug-induced injury. She has remained well with good graft function at 1-year follow-up. The case highlights an extreme form of drug-induced ductopenia and underscores the need for meticulous hepatology input and consideration of liver transplantation in some patients.